Fun Reading App Berbasis Multimedia Interaktif untuk Meningkatkan Kemampuan Membaca Permulaan - Dian Andriani; Khaeroni; Imas Mastoah (PrimEarly : Jurnal Kajian Pendidikan Dasar dan Anak Usia Dini, 2022)
Students with moderate mental-retardation tend to choose learning that is concrete and interesting, as well as learning to read. Learning that is not in accordance with these tendencies has an impact on early reading skills also reduces the level of concentration of students thereby weakening students' opportunities to remember. This research was conducted to produce Fun Reading App, that is an interactive multimedia-based. It is hoped that this product can improve students’ early reading skills with moderate mental-retardation. Product is produced through research and development procedures according to the ADDIE model. The validity testing involves three experts and for the product effectivity test involves 4 students. The research shows: 1) the validity test of the product is in the criteria of valid or usable; and 2) the product effectiveness test with the Gain test is on the N-Gain score with high criteria.